Diabetes treatment in people with type 2 diabetes and schizophrenia: Retrospective primary care database analyses. Issue 1 (February 2016) - Rathmann, Wolfgang; Pscherer, Stefan; Konrad, Marcel; Kostev, Karel
Highlights: Diabetes patients with and without schizophrenia were retrospectively analyzed. There was no difference in the mean HbA1c values and in the average BMI. Schizophrenia was not associated with use of novel antidiabetic agents. Abstract: Aims: Aim of this study were to compare outcomes (HbA1c, BMI) and antidiabetic treatment of type 2 diabetes patients with and without schizophrenia under real-life conditions in primary care practices in Germany. Methods: 1321 type 2 diabetes patients with and 1321 matched controls (age, sex, diabetes duration, diabetologist care, practice) without schizophrenia in 1072 general practices throughout Germany were retrospectively analyzed (Disease Analyser: 01/2009–12/2013). Antidiabetic treatment, HbA1c and BMI were compared using paired t -tests, McNemar tests and conditional logistic regression adjusting for macro- and microvascular comorbidity (ICD-10). Results: Mean age (±SD) of patients and controls was 67.4 ± 13.2 years (males: 38.9%). Diabetes duration was 5.7 ± 4.3 years, 6% were in diabetologist care. Private health insurance was less often found among patients with schizophrenia than controls (2.2% vs 6.3%; p < 0.0001). There was no difference in the mean HbA1c values (cases: 7.1 ± 1.4%; controls: 7.2 ± 1.5%) (54.1 vs. 55.2 mmol/mol) ( p = 0.8797) and in the average BMI (32.4 ± 6.6 vs. 31.0 ± 5.0 kg/m 2 ; p = 0.2072) between the two groups. Novel cost-intensive antidiabetic agents (DPP-4- or SGLT2-inhibitors, GLP-1 receptor agonists) were less often prescribed in cases (15.3 vs. 18.3%; p = 0.0423). However, in multivariable logistic regression, schizophrenia (odds ratio, 95%CI: 1.101; 0.923–1.317) was not associated with prescription use of novel antidiabetic agents (reference: other antidiabetic agents) after adjusting for private health insurance (OR: 2.139; 1.441–3.177) and comorbidity. Conclusions: There is no evidence that type 2 diabetes patients with schizophrenia have worse diabetes control than those without a severe mental illness in general practices.